2011
DOI: 10.1016/j.physletb.2011.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb excitation of 31Mg

Abstract: Link to publication in University of Groningen/UMCG research database Citation for published version (APA): Seidlitz, M., Muecher, D., Reiter, P., Bildstein, V., Blazhev, A., Bree, N., ... Wiens, A. (2011). Coulomb excitation of , 181-186. https://doi.org/10.1016/j.physletb.2011.05.009 Copyright Other than for strictly personal use, it is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), unless the work is under an open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 46 publications
6
42
0
Order By: Relevance
“…This is probably related to the underbinding of the sd-shell calculations when valence neutron-neutron interactions are dominant. We also note that around N = 20, the ground states of 29,30 Ne [44,45], 30,31 Na [46,47], and 31,32 Mg [48,49] are dominated by deformed configurations not captured in our sd-shell calculations (this is the so-called island of inversion). Consequently, our bands do not reproduce the change in slope of S 2n around N = 20 for Ne, Na, or Mg.…”
mentioning
confidence: 86%
“…This is probably related to the underbinding of the sd-shell calculations when valence neutron-neutron interactions are dominant. We also note that around N = 20, the ground states of 29,30 Ne [44,45], 30,31 Na [46,47], and 31,32 Mg [48,49] are dominated by deformed configurations not captured in our sd-shell calculations (this is the so-called island of inversion). Consequently, our bands do not reproduce the change in slope of S 2n around N = 20 for Ne, Na, or Mg.…”
mentioning
confidence: 86%
“…This value corroborates the findings from the ground-state configuration with its intruder configuration. The given values comprise results from experiments performed at RIKEN [58,62], MSU [59,60], GANIL [59,60] and at ISOLDE employing safe CE [11,13,63] and the fast-timing technique after β decay [64]. While for  N 18 the experimental values are well reproduced by USD shell-model calculations [65], large deviations are found for  N 20.…”
Section: The Island Of Inversionmentioning
confidence: 99%
“…The initial physics program suggested by the proposal for the MINIBALL at REX-ISOLDE started with a thorough investigation of neutron-rich Na and Mg nuclei in the vicinity of the N=20 shell by means of Coulomb excitation (CE) and neutron-transfer reactions [10][11][12][13][14][15]. Simultaneously experiments along the chains of neutron-rich Ni, Cu and Zn isotopes were pursued in order to study collective and single particle properties in the vicinity of N=40 and the doubly-magic configuration at 78 Ni [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…For Doppler correction, all angles of the cluster detectors had to be known exactly. Therefore an angle-calibration measurement was performed, using Dopplershifted γ rays after the neutron pick-up reaction d( 22 Ne, 23 Ne)p. The high segmentation of the setup ensured a proper Doppler correction for in-flight γ -ray emission at v/c ∼ 8% by combining the angular information of the γ ray with the direction and velocity of the scattered beam particle that was detected in coincidence. Data of the Coulomb-excitation measurements were recorded using prompt particle-γ coincidences, i.e., events with a maximum time difference of typically 800 ns between particle and γ ray were registered.…”
Section: Experimental Setup and Data Analysismentioning
confidence: 99%
“…More recently it could be confirmed that already at N = 19 the wave functions of the ground and low-lying states contain a dominant admixture of intruder configurations [21][22][23]. For the neighboring N = 18,19 Na isotopes, 29,30 Na, measurements of the magnetic dipole moments and electric quadrupole moments revealed significant deviations from the universal sd-shell (USD) model [24,25], indicating a dramatic change in the underlying shell structure also for these nuclei.…”
Section: Introductionmentioning
confidence: 99%